TINJAUAN KAUSALITAS INDIKATOR MAKROEKONOMI DI PROVINSI BENGKULU - Barika Barika; Armelly Armelly; Benardin Benardin (Convergence: The Journal of Economic Development, 2020)
The aims of this research are to determine the statistical causality between poverty, education level, economic growth, investment and income inequality in Bengkulu province. To analyze how the influence of education level, economic growth, investment and income inequality on poverty in Bengkulu province. This research are use granger causality test method and Panel Multiple regression. The result shows the variables have causal relations are income inequality with economic growth, income inequality with investment. Panel data regression results show that education, economic growth, and investment variables significantly influence poverty in Bengkulu province. Keywords :  Granger Causality1, Education2, Economic Growth3, Invesment 4, Poverty 5